2011
DOI: 10.1039/c0mt00048e
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal imaging with high spatial resolution: Applications in biomedicine

Abstract: New generations of analytical techniques for imaging of metals are pushing hitherto boundaries of spatial resolution and quantitative analysis in biology. Because of this, the application of these imaging techniques described herein to the study of the organization and dynamics of metal cations and metal-containing biomolecules in biological cell and tissue is becoming an important issue in biomedical research. In the current review, three common metal imaging techniques in biomedical research are introduced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 52 publications
0
134
0
Order By: Relevance
“…Zinc exists as a divalent cation (Zn 2ϩ ) and is not redox active under physiological conditions, which explains why zinc performs multifarious physiological roles in a variety of biological processes (TABLE 1). This feature of Zn 2ϩ hampered its detection, and clarification of the dynamic state of zinc was a challenge until recent improvements in zinc-imaging techniques became available, including small fluorescent sensor molecules, FRET molecules designed to sense zinc ions, X-ray fluorescence microscopy, and laser ablation inductively coupled, plasma mass spectrometry (99,174,335,338,412,425).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc exists as a divalent cation (Zn 2ϩ ) and is not redox active under physiological conditions, which explains why zinc performs multifarious physiological roles in a variety of biological processes (TABLE 1). This feature of Zn 2ϩ hampered its detection, and clarification of the dynamic state of zinc was a challenge until recent improvements in zinc-imaging techniques became available, including small fluorescent sensor molecules, FRET molecules designed to sense zinc ions, X-ray fluorescence microscopy, and laser ablation inductively coupled, plasma mass spectrometry (99,174,335,338,412,425).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that spatially resolved LA-ICP-MS can be employed to visualize the distribution of silver and gold nanoparticles in single cells (Figure 13.5) [85]. Beside the ease of calibration in element quantification, the multielement detection with high sensitivity and high spatial resolution makes LA-ICP-MS well-suited for single-cell analysis [79,[86][87][88].…”
Section: Quantification Of Metal Nanoparticles In Cellsmentioning
confidence: 99%
“…Two important fields in which Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS) is experiencing growing demand are those of imaging/mapping, notably of biological targets [1][2][3][4][5][6] and the analysis of discrete smallvolume samples such as single cells [7][8][9][10][11] or nanoparticulate [12][13][14] . For example this technique has been used to investigate the etiology and pathogenesis of disease states arising from imbalances in metal homeostasis.…”
Section: Introductionmentioning
confidence: 99%